The Amazing Circulatory System - Slim Goodbody (New York, Canada Crabtree Publishing Co,Canada, 2009)
Here, children will learn how the amazing heart muscle works. They will discover how blood vessels transport life-giving oxygen to the cells and carry away carbon dioxide.
Keywords: Who We Are -- -Body Systems